Automatic Triangulation for Planar Domain - NI Pei-tong; JIANG Wei (Renmin Zhujiang)
This paper presents the principle of the least angle and the largest side by using the method of advancing front to generatethe triangular element for planar domain. The triargular meshes generated have been applied to the numerical modeling for Sixianjiaoand satisfactory results have been achieved.